(untitled) (Sains Humanika, 2025)
During the COVID-19 pandemic, social media platforms in Indonesia experienced a significant increase in total users, leading to a higher risk of addiction to social media and the internet compared to typical situations. Social media platforms also introduced new features that enabled novel ways of interacting during the pandemic. However, the use of various social media by adolescents remain underexplored. This study aims to provide a comprehensive overview of the problematic social media use in adolescents, comparing those based on the number of social platforms they actively use, such as Instagram, TikTok, and Twitter. We conducted an offline survey on a sample of 207 Indonesian junior and senior high school students (aged 10–19) from Jakarta, Bogor, Depok, Tangerang, and Bekasi. Data were collected using the Internet Addiction Test (IAT) and a demographic questionnaire. A one-way ANOVA revealed significant differences in PSMU among adolescents who actively use one, two, or three social media platforms. Adolescents who actively use three platforms tended to have higher PSMU levels. These findings highlight the need for targeted interventions that address adolescents’ social media usage patterns to reduce the risks associated with excessive use.